Good Corporate Governance Affects on Corporate Value Through Return on Equity and Return on Asset of Manufacture Company - Kumalasari, D; Pratikto, H (KnE Social Sciences, 2018)
This study aims to determine the direct effect of GCG on Corporate Value, GCG of the ROA, ROE on Corporate Value, ROA of the Corporate Value and to determine the indirect effect of the GCG on Corporate Value through ROE and ROA. By using path analysis research show that: 1) the condition of Corporate Values and ROA variables are classified low, while the variable conditions of GCG and ROE are medium, 2) GCG has a significant positive effect on Corporate Value, 3) GCG has a significant positive effect on ROE, 4) ROE has a significant positive effect on Corporate Values, 5) GCG has a positive effect significantly on ROA, 6) ROA significant positive effect on the Corporate Values. Thus in this study, ROE and ROA is a mediating variable between GCG influence on the value of the Company. Keywords: good corporate governance, Tobin’s q, return on equity, return on asset, corporate value.